Palladium‐Catalyzed Alkoxy‐ and Aminocarbonylation of α‐Halomethyl Oxime Ethers: Synthesis of 1, 3‐Alkoxyimino Esters and 1, 3‐Alkoxyimino Amides. Issue 2 (29th December 2014) - Noverges, Bárbara; Medio‐Simón, Mercedes; Asensio, Gregorio
Abstract: α‐Halomethyl oxime ethers react in palladium‐catalyzed three‐component reactions with alcohols or amines and carbon monoxide (CO) at atmospheric pressure to afford efficiently novel β‐oxyimino esters or β‐oxyimino amides, respectively. The reactions proceed with total regiocontrol, excellent yield, and high atomic economy regarding the reagents from simple commercially available starting materials using 10 mol% palladium(II) acetate [Pd(OAc)2 ]/7 mol% Xantphos as catalyst. Direct nucleophilic substitution at the very reactive α‐halomethyl moiety was noticeable only in the preparation of β‐oxyimino amides derived from alkylamines. In this case, β‐oxyimino amides are obtained alternatively by a one‐pot two step alkoxycarbonylation/ester aminolysis process. Site selective alkoxy‐ and aminocarbonylation reactions of bromoaryl‐substituted α‐halomethyl oxime ethers at the C sp 3 Br bond are described. Abstract :